1998
DOI: 10.1042/bj3350175
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that mammalian phosphatidylinositol transfer protein regulates phosphatidylcholine metabolism

Abstract: Phosphatidylinositol transfer proteins (PITPs) and their yeast counterpart (SEC14p) possess the ability to bind phosphatidylinositol (PtdIns) and transfer it between membranes in vitro. However, the biochemical function of these proteins in vivo is unclear. In the present study, the physiological role of PITP was investigated by determining the biochemical consequences of lowering the cellular content of this protein. WRK-1 rat mammary tumour cells were transfected with a plasmid containing a full-length rat P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
14
2
Order By: Relevance
“…Microinjection of fluorescently labeled PI-TPa and PI-TPb into living cells as well as indirect immunofluorescence studies have shown that PI-TPa is localized in the nucleus and cytosol whereas PITPb is associated with the Golgi system [8]. In intact cells, decreased expression of PI-TPa was shown to decrease the rate of proliferation and a lower rate of synthesis was observed for PC, lysoPC, SM, Choline and Glycerophosphocholine [9]. However, knock out of PI-TPa in mouse embryonic stem cells fails to compromise growth and has no significant consequence for bulk phospholipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Microinjection of fluorescently labeled PI-TPa and PI-TPb into living cells as well as indirect immunofluorescence studies have shown that PI-TPa is localized in the nucleus and cytosol whereas PITPb is associated with the Golgi system [8]. In intact cells, decreased expression of PI-TPa was shown to decrease the rate of proliferation and a lower rate of synthesis was observed for PC, lysoPC, SM, Choline and Glycerophosphocholine [9]. However, knock out of PI-TPa in mouse embryonic stem cells fails to compromise growth and has no significant consequence for bulk phospholipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…A role for PITP␣ in regulating metabolism of choline phospholipids in mammalian cells has also been proposed. Antisense approaches suggest that modest reductions in PITP␣ levels result in significant alterations in PtdCho and SM metabolism in one breast cancer cell line (Monaco et al, 1998).…”
Section: Choline Phospholipid Metabolism In Pitp␣-deficient Cellsmentioning
confidence: 99%
“…In mammalian tissues, at least two isoforms are identified: PI-TP ␣ , which is localized in the nucleus and cytosol, and PI-TP ␤ , which is associated with the Golgi system (3). Possible cellular functions of these proteins have been obtained from experiments with permeabilized cells (4), reconstituted Golgi membrane systems (5), and cells in which the expression of the proteins has been altered (6)(7)(8). In permeabilized, cytosol-depleted cells, both isoforms restored guanosine 5 Ј -[ ␥Ϫ thio]triphosphate-stimulated protein secretion as well as phospholipase C-mediated inositol lipid signaling (9)(10)(11).…”
mentioning
confidence: 99%